Associations Between Six Core Processes of Psychological Flexibility and Functioning for Chronic Pain Patients: A Three-Level Meta-Analysis - Ding, Dongyan; Zheng, Mengna (Frontiers in Psychiatry, 2022)
The previous research showed contradictions in the relationships between psychological flexibility processes and functioning. This meta-analysis is the first to provide a comprehensive meta-analysis of the associations between six core processes of psychological flexibility and functioning among chronic pain patients. Four databases were searched (PsycINFO; PubMed; CINAHL; Web of Science) along with reference lists. Thirty-six cross-sectional studies were included (7812 chronic pain patients). A three-level meta-analytic model was used to examine the associations. The publication bias was assessed with the Egger test, funnel plot, and p-curve analysis. Significant associations were found between functioning and six processes of psychological flexibility (i.e., acceptance, defusion, present moment, committed action, self as context, and values). Except for the relationship between defusion and functioning, the relationships between the other five psychological flexibility processes and functioning were all moderated by domains of functioning. No moderators were found regarding age, percentage of females, country, or type of instrument used to measure functioning. These findings may carry significant implications for chronic pain patients and clinical workers. It might be more effective to focus on functioning-related psychological flexibility processes rather than all therapy packages if the relationships between functioning and specific processes of psychological flexibility were better informed. Limitations were also discussed.